Fostering public climate change discussions from a social interaction perspective - Tian, Jianchi; Zheng, Xiaoqing; Sun, Yan (Frontiers in Psychology, 2023)
Public discussions on climate change, as a form of social interaction, are widely recognized as effective tools for promoting collective action. However, there is limited research on examining the factors that influence climate change discussions from a social interaction perspective. In the present study, we conducted a large sample (N = 1,169) survey to investigate personal (such as self-efficacy and personal response efficacy) and others' (such as perceived others' response efficacy and social norms) factors influencing climate change discussions from a social interaction perspective. The results showed that (i) for people with high climate change perceptions, personal response efficacy, self-efficacy, and social norms have positive effects on climate change discussions, but the effect of perceived others' response efficacy on climate change discussion is not significant; (ii) for people with low climate change perceptions, self-efficacy and social norms have positive effects on climate change discussions, but the effects of personal response efficacy and perceived others' response efficacy on climate change discussion are not significant; (iii) irrespective of individuals' high or low perceptions of climate change, social norm remains the most important predictor of climate change discussions. These findings make valuable contributions to the theoretical literature and intervention efforts regarding climate change discussions from a social interaction perspective.